Digital Zooarchaeology: State of the art, challenges, prospects and synergies. (October 2022) - Spyrou, A.; Nobles, G.; Hadjikoumis, A.; Evin, A.; Hulme-Beaman, A.; Çakirlar, C.; Ameen, C.; Loucas, N.; Nikita, E.; Hanot, P.; de Boer, N.M.; Avgousti, A.; et al.
Highlights: The article provides a snapshot of the current state of art, the methods and digital tools being employed in the digitisation of animal remains. Digital technologies have the capacity to democratise science by making knowledge available to academic and non-academic audiences. Digital twins are fundamental in Zooarchaeology because they allow us to explore new methods and approaches (e.g. 3D Geometric Morphometrics) that do not require access to the physical object. The article raises some of the challenges that the international zooarchaeological community is facing in the era of Linked Open Data, including management, archiving, curation, storage, dissemination and communication of digital data to the scientific world and the wider public. The article calls for a better coordination and collaboration between Digital Archaeologists and Zooarchaeologists. Abstract: Digital technologies are an increasingly pervasive medium for zooarchaeological scholarship, providing a means to document and preserve fragile zooarchaeological specimens, share primary data, address methodological questions, and spread the information to the wider public. During the last decade, a broad array of digital technologies has been widely applied for the creation of three-dimensional images of animal bones, with a number of freely accessible collections being developed and published online. To be beneficial for academic and non-academic audiences, the creation of these collections requires careful planning, and more attention is needed in order to ensure their longevity in the web as well as their future usability. Drawing on an online workshop, organised by the Science and Technology in Archaeology and Culture Research Center of The Cyprus Institute, titled "Zooarchaeology in the Digital Era", this article aims to provide a snapshot of the current state of art, and the methods and digital tools being employed in the digitisation of animal remains. The article also raises some of the challenges that the international zooarchaeological community is facing in the era of Linked Open Data, including management, archiving, curation, storage, dissemination and communication of digital data to the scientific world and the wider public. In addition, the paper highlights the need for a stronger collaboration between archaeologists and researchers from the Digital Humanities' sector in order to stimulate an innovative discourse and create fertile ground for the production of new scientific knowledge.